Innovation today: the Triple Helix and research diversity - Alain-Marc Rieu (Triple Helix, 2014)
Innovation policies are considered the long-term strategy to overcome the present systemic crisis. But this crisis is questioning such policies, their presuppositions and institutional arrangements. This questioning includes the Triple Helix theory and its impact on research and innovation policies. The goal is to examine how this theory can respond to theoretical and practical challenges, how the theory needs to evolve in order to fit the present context. The criticism focuses on growing worldwide standardization of research and innovation policies and their long-term impact on innovation. Restoring and increasing research diversity is urgent for sustained innovation. One solution is to add 'society' as a fourth helix. The problem is to clarify what 'society' stands for in this context. The paper studies three different institutional arrangements, France, Germany, and Japan, because these three cases can learn from each other and contribute to progress in the Helix theory itself. Potential reforms are summarized in some policy recommendations.
Keywords: 330; Triple Helix; Diversity; Allemagne; Diversité; Fourth helix; France; Germany; Governance; Innovation territories; Institution; Institutions; Japan; Japon; Politique de recherche; Quatrième hélix; Research policy; Territoires d'innovation